Phenolic compounds from irradiated olive wastes: optimization of the heat-assisted extraction using response surface methodology - Madureira, Joana (2021)
Olive pomace, an environmentally detrimental residue generated during olive oil extraction, contains bioactive compounds in demand by the food industry. To valorize this waste product a suitable yield for the extraction process is required. Heat-assisted extraction of bioactive compounds from olive pomace was optimized by a circumscribed central composite design and response surface methodology. Our previous studies indicated that irradiation could improve 2.4-fold the extractability of the main phenolic compounds from olive pomace. The effect of extraction time, temperature and solvent concentration on the yield of polyphenols from irradiated olive pomace at 5 kGy was tested. Hydroxytyrosol-1- -glucoside, hydroxytyrosol, tyrosol and caffeic acid were quantified by High Performance Liquid Chromatography to calculate the total polyphenol content. The optimal general conditions by RSM modeling were extraction time of 120 min, temperature of 85 C, and 76% of ethanol in water. Using these selected conditions, 19.04 1.50 mg/g dry weight, 148.88 8.73 mg/g extract of total polyphenols were obtained, representing a yield of 13.7%, which was consistent with the value predicted by the model. This work demonstrated the potential of residues from the olive oil industry as a suitable alternative to obtain compounds that could be used as ingredients for the food industry.